Knowledge of Critical Care Unit Nurses Regarding Care of Patient with Hemorrhagic Fever (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Hemorrhagic fevers are severe viral infections that cause vascular damage, multiorgan dysfunction, and high mortality rates, posing a major challenge to healthcare systems, particularly in resource-limited settings. Nurses working in intensive care units (ICUs) are at the forefront of managing these infections; thus, their knowledge of infection prevention and control (IPC) measures is critical for effective patient care and containment of disease spread. This study aimed to assess ICU nurses’ knowledge regarding hemorrhagic fever and related IPC practices. A descriptive exploratory design was employed, including 184 nurses who completed a validated, self-administered questionnaire developed through literature review and expert evaluation for content validity and clarity. The findings revealed that most participants demonstrated adequate awareness of infection control principles: 85.3% recognized that hand hygiene is necessary before and after procedures, and 98.9% understood that it helps prevent hospital-acquired infections. Additionally, 98.9% of nurses were aware that the primary role of personal protective equipment (PPE) is to protect healthcare workers and minimize pathogen transmission. However, 73.8% of participants showed insufficient knowledge regarding the consistent application of standard precautions to all patients, indicating a significant gap in practice-related understanding. Overall, 51.3% of the nurses achieved a satisfactory knowledge level regarding hemorrhagic fever. Higher knowledge scores were significantly associated with older age, higher educational attainment, and longer years of professional experience, while gender showed no significant relationship. The study concludes that although nurses exhibit good awareness of key IPC measures, deficiencies in understanding standard precautions highlight the need for regular, targeted training programs and continuous education to strengthen infection control practices within intensive care units.